Pengembangan E-Modul Berbasis RME Materi Bangun Ruang Menggunakan Aplikasi Book Creator Untuk Siswa Kelas V Sekolah Dasar - Fitri Yusroh; Nora Surmilasari; Jayanti Jayanti (Jurnal Binagogik, 2024)
The era of revolution 5.0 is a time when technology has a major impact on all lines of life, including education. Therefore, the development of RME-based e-modules for building space materials using the book creator application for grade V students, becomes a challenge as well as an opportunity to actively participate in future journeys. Based on this, the problem in this study is how to develop a valid and practical e-module. The purpose of this study is to determine the feasibility of using e-modules in learning. The type of research used by researchers in developing this RME-based e-module is research and development (R&D) referring to the ADDIE model. Based on expert tests from validators covering three aspects, namely media, language, and material, the results of this study obtained an average percentage of 89.33% with the category "very valid" then supported by the results of direct student trials (one to one) and obtained a percentage of 93.33% with the category "very valid". Then, the last trial was a trial in a small group with an average gain of 90.86% categorized as "very practical" which was supported by the teacher's response to obtaining a questionnaire percentage of 93.26%.